The Existence of Pancasila Ideology in the KKNI Curriculum and its Implementation at the Faculty of Law, Airlangga University, and The Faculty of Sharia and Law, State Islamic University of Sunan Ampel Surabaya - Damanhuri, Damanhuri; yasin, Ikhsan fatah (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
Pancasila as a guideline for the nation's life is manifested in every aspect of Indonesian society. In the field of education, the existence of Pancasila is concretized in the KKNI curriculum. So, how is the existence of the Pancasila ideology in the Legislation that underlies the KKNI Curriculum, especially in higher education? This study aims to examine the existence of Pancasila in the KKNI curriculum, especially in the implementation of the KKNI curriculum at the Faculty of Law, Airlangga University, and the Faculty of Sharia and Law, UIN Sunan Ampel Surabaya. The research method used in this study is the empirical normative method. Based on the results of the study, it was revealed that the legislation that is the legal basis for the KKNI curriculum already reflects the values of Pancasila and strengthens Pancasila's ideology in organizing the learning process in higher education. This appears in the general description and gradation of the KKNI in Presidential Regulation Number 8 of 2012 and also the Learning Outcomes (CPL) in the attachment to the Regulation of the Minister of Research and Higher Education Number 44 of 2015 on the aspect of general attitudes and skills. These learning outcomes and general skills aspects serve as a guideline for all higher education providers when creating the KKNI curriculum structure. The KKNI curriculum at the Faculty of Sharia and Law and the Faculty of Law UNAIR has strengthened the ideology of Pancasila. The steps are by referring to the CPL in the attachment to the Regulation of the Minister of Research and Higher Education No. 44 of 2015 and adding the university's vision and mission as a Characteristic of Higher Education. Furthermore, several courses are formed that intensively discuss Pancasila and also through the learning process carried out by the lecturers in charge of the courses by instilling the values of Pancasila.